MOSAIC: A cohort study of human mpox virus disease [version 2; peer review: 2 approved] - Yazdan Yazdanpanah; Laura Merson; F-Xavier Lescure; Amanda Rojek; Alexandra Calmy; Piero Olliaro; Josephine Bourner; Isabelle Hoffmann; Peter Horby; Elise Pesonel; Alpha Diallo; Laetitia Guiraud; et al. (Wellcome Open Research, 2023)
Background Human mpox is a viral disease caused by an Orthopoxvirus, human mpox virus (hMPXV), typically causing fever and a rash. Mpox has historically been endemic to parts of Central and West Africa, with small numbers of imported cases reported elsewhere, but starting May 2022 an unprecedented global outbreak caused by clade IIb hMPXV was reported outside traditionally endemic countries. This prompted the initiation of MOSAIC, a cohort study implemented in Europe and Asia that aims to describe clinical and virologic outcomes of PCR-confirmed hMPXV disease, including those who receive antiviral therapy. The study is ongoing. Methods MOSAIC recruits participants of any age with laboratory-confirmed mpox disease who provide informed consent. Participants enrol in the cohort for a total of six months. Blood, lesion and throat samples are collected at several timepoints from the day of diagnosis or the first day of treatment (Day 1) until Day 28 for PCR detection of hMPXV. Clinical data are collected by clinicians and participants (via a self-completion questionnaire) for six months to characterize the signs and symptoms associated with the illness, as well as short- and more long-term outcomes. Discussion The design and prompt implementation of clinical research response is key in addressing emerging outbreaks. MOSAIC began enrolment within two months of the start of the international mpox epidemic. While the number of cases is now low, the study remains open for inclusion. ICTRP registration EU CT number: 2022-501132-42-00 (22/06/2022)